Clinical significance of CCNE1 copy number gain in acral melanoma patients. Issue 4 (August 2021) - Wu, Xiaowen; Yan, Junya; Yu, Jiayi; Cheng, Zhiyuan; Guo, Qian; Kong, Yan; Guo, Jun
Abstract : Copy number variations are frequently observed in cell cycle–related genes in acral melanoma. However, the clinical significance of copy number gain of CCNE1 in acral melanoma has not been fully elucidated. In this study, 490 acral melanoma samples were examined for CCNE1 copy number using the QuantiGenePlex DNA Assay. Correlation between CCNE1 copy number and acral melanoma patients' clinicopathologic features were analyzed using Chi-squared test. The impact of CCNE1 copy number on patients' progression-free survival (PFS) and overall survival (OS) probability were analyzed using Kaplan–Meier analysis. The impact of CCNE1 copy number on patients' median PFS after receiving chemotherapy was also evaluated. The results showed that CCNE1 copy number gain was observed in 28.30% of patients, with 3.16% of patients carrying both CCNE1 copy number gain and BRAF mutation and 4.34% of patients carrying both CCNE1 copy number gain and NRAS mutation. The median PFS time for patients with CCNE1 copy number gain was shorter than that of patients without CCNE1 copy number gain (17.0 vs. 27.0 months, P = 0.002).In the cohort that received chemotherapy ( n = 82), the median PFS time for patients with CCNE1 copy number gain was shorter than that of patients without CCNE1 copy number gain (4.8 vs. 7.4 months, P = 00.006). CCNE1 copy number gain was an independent prognostic marker for acral melanoma patients' PFS. Our study indicates that CCNE1 copy number gain is frequent in acral melanoma and may be a biomarker to predict acral melanoma patients' outcomes after receiving chemotherapy. Abstract : Supplemental Digital Content is available in the text.